Primary School Student Teachers’ Perceived and Actual Knowledge in Biology - Yli-Panula Eija; Jeronen Eila; Pongsakdi Nonmanut (Faculty of Education, University of Ljubljana, 2022)
Individuals’ perceptions of their knowledge can have an important role in shaping their cognition and influencing their behaviour. However, there has been a scarcity of studies in biology on how perceived knowledge relates to actual knowledge. The focus of this article is on quantitative results analysing and interpreting student teachers’ perceived knowledge of biological content in relation to their actual animal and species name knowledge linked to the ecosystem in which they live. K-means cluster analysis and ANOVA were used. The results show a high- and low-level perceived knowledge cluster group among the participants. They further indicate that the difference in actual animal and species name knowledge between these cluster groups remained the same during the five years of the study. The student teachers with a higher level of perceived knowledge tended to have better actual animal and species name knowledge than those in the low-level group. The actual animal name knowledge in these cluster groups was similar with regard to the local Finnish ecosystems but differed concerning the exotic species by year. The year that the participants enrolled in the study programme had an impact on their actual animal and species name knowledge. Strategies for coping with work-related demands and maintaining engagement in one’s career would be important additions to the teacher education curriculum.